Restaurants, fields, markets, and feasts: Food and culture in semi-public spaces. Issue 3 (1st October 2016) - Sammells, Clare A.; Searles, Edmund (Ned)
ABSTRACT: The articles presented in this special issue explore connections between food and meaning at the intersection of public and private spaces. They highlight the myriad ways in which food and eating practices shape indigenous, national, religious, and immigrant identities. They engage global politics, define and contest the boundaries of community, and discuss new spaces of economic exchange and sociality. The contributors engage emerging constructions of "fieldwork, " "the field, " and place. They consider the challenges and rewards of conducting fieldwork in semi-public culinary spaces, often crossing—sometimes transgressively, always meaningfully—boundaries between public and private, national and transnational, local and global.